PELATIHAN PEMBELAJARAN STEM DI SEKOLAH DASAR UNTUK MENGEMBANGKAN KETERAMPILAN ABAD 21 - Handayanto, Supriyono Koes; Oktarianto, M Luthfi; Yasa, Arnelia Dwi; Setiyawati, Enik; Isbandrianingtyas, Nafi (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
Today's problem in STEM learning is that STEM-based learning has not been carried out optimally. Most of the teachers experienced many problems related to IT-based media. In addition, the form of HOTS-based learning evaluation has not been fully mastered by the teacher. This training aims to improve the skills of teachers in STEM learning at the primary school level. Implementing the activities carried out are workshops, mentoring, and evaluation. The target participants consisted of 16 teachers from the Malang City cluster one primary school. The results of this training show an increase in the skills of teachers with STEM learning. The indicators that as many as 16 teachers have made STEM-based learning media according to the material in elementary schools. However, all the results of the teacher's products require minor improvements. The trainees' response also showed a positive response in STEM learning training in elementary schools to develop skills in the 21st century.